Peranan Self Efficacy dalam Memediasi Human Capital terhadap Kinerja Karyawan Laut pada PT. ASDP Indonesia Ferry (Persero) Cabang Selayar - Haryadi, Nur; Amir, Amir (Study of Scientific and Behavioral Management (SSBM), 2024)
ABSTRACT This research aims to determine the influence of human capital on self-efficacy, human capital on the performance of marine employees, the influence of self-efficacy on employee performance, and the influence of self-efficacy as an intervening variable in mediating the relationship human capital on the performance of marine employees at PT ASDP Indonesia Ferry (Persero) Selayar Branch. The sample collection technique used was the saturated sample technique. The type of research used is explanatory research. The data source used is primary data, by distributing questionnaires to respondents to fill in. The number of samples used was 113 respondents. The data processing method used in this research uses SmartPLS software. The results of the research show that human capital has a positive and significant effect on self-efficacy, human capital has a positive and significant effect on employee performance, self-efficacy has a positive and significant effect on employee performance, and the intervening variable self-efficacy has a positive and significant effect in mediating the effect of human capital on performance. marine employees. Key words: human capital, self efficacy, employee performance.